Status and economy of community fi sh farming in rural Odisha - Radheyshyam, .; Saha, Gour Sundar; De, Himansu Kumar; Safui, Lekha; Eknath, A. E.; Adhikari, Subhendu; Barik, Nagesh Kumar; Chandra, Suresh (Indian Journal of Fisheries, 2013)
An investigation on community fi sh farming and its economy was carried out in eighty-one randomly chosen typical community fi sh ponds from two representative districts (Khurda and Puri) of rural Odisha. Study reveals a low level of technological adoption of aquaculture with very traditional and extensive methods of carp culture, which may be termed as rural aquaculture. The lease arrangement was the predominant institutional arrangement with lease period of 1, 3 and 5 years and the respective fi sh production of 769, 930 and 1634 kg ha-1yr-1. It was found that the system responded quite well to the changes in the technology and management. The impact of a few management measures was found to be positive on the fi sh productivity improvement. Presence of aquatic macrophytes, weed and predatory fi shes, under-dose manure and fertilizer application and/or no use of manure and fertilizer, stocking of small size fi sh seed in unprepared ponds, under feeding and/or not feeding to fi sh had adverse effect on fi sh production and net income generation in village community ponds. There was signifi cant increase in fi sh production (p